Study Lecturer’ ICT Skill in Teaching and Learning Implementation at Luang Prabang Teacher Training College, Academic year 2024-2025 - KHONESAVATH , Panomphone; KOUNLAXAY , Kalaphath; THIPPHAPHONE, Kinnaly (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research is a quantitative and qualitative research through the participatory research process of teachers in Luang Prabang Teachers College, which aims to: 1) To study the results of using ICT in the teaching and learning of teachers in Luang Prabang Teachers College. 2) To study the development of ICT skills according to the standards of ICT teachers in the Lao PDR. The research target group this time is 104 people, using the study method to analyze documents, related research, using questionnaires to collect data directly from teachers. Data analysis uses a quantitative analysis method, to lead to the explanation of the results in a causal manner to the reality of the data as much as possible. The research result found that the ICT skills development of teachers in Luang Prabang Teachers' College was at a very high level = 3.86 S.D. = 0.84, where the ICT skills had a higher mean value = 4.04 S.D. = 0.84; followed by computer skills = 3.86 S.D. = 0.84 and ICT skills in teaching = 3.74 S.D. = 0.84; and the Internet skills had the lowest mean value = 3.72 S.D. = 0.86. Guidelines for the development of ICT skills of teachers in Luang Prabang Teachers' Training College Administrators should disseminate or introduce basic computer skills to teachers in schools, organize teacher competence assessment in the initial stage, plan and prepare for internal training or invite external experts, promote and cooperate with personnel to develop themselves in various areas, and provide opportunities for teachers to share lessons with each other.